Hungarian Monitoring, 22 February 1990 . [Magyar rádiófigyelő], 1990. február 22 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Václav Havel in America - German unity: supplies in the GDR - USSR: Soviet troop withdrawals from Czechoslovakia, the danger of fascism, internal conflicts - Gabčíkovo-Nagymaros dam - Romania: national questions, András Sütő, book transports, Vlad Socor (RFE) - Israeli foreign relations - Gyula Horn: NATO, reactions - Disarmament talks in Vienna Domestic Affairs: - Elections: mass rallies, programs, opposition parties - Soviet troop withdrawals from Hungary - Political prisoners - Workers' Militia in Székesfehérvár Economy: - IMF loan - Budapest-Vienna World Exposition - Medicor Külpolitika: - Václav Havel Amerikában - Német egyesítés kérdése: ellátás az NDK-ban - Szovjetunió: csapatok kivonása Csehszlovákiából, fasizmus veszélye, belső konfliktusok - Bősi vízlépcső - Románia: nemzeti kérdés, Sütő András, könyvszállítmányok, Vlad Socor (SZER) - Izrael: külkapcsolatok - Horn Gyula: NATO, reakciók - Leszerelési tárgyalások Bécsben Belpolitika: - Választás: nagygyűlések, műsorok, ellenzéki pártok - Szovjet csapatok kivonása Magyarországról - Politikai elítéltek kérdése - Munkásőrség Székesfehérváron Gazdaság: - Nemzetközi Valutaalap hitel - Budapest-Bécs Világkiállítás - Medicor